Time since last birth and the risk of endometrial cancer: A meta-analysis of observational studies - Gu, Juan; Lai, Yuchen; Shou, Huafeng; Wang, Liping (PloS one, 2025)
Endometrial cancer, an adenocarcinoma originating from the uterine lining, is the most prevalent cancer of the female genital tract globally.Identifying early risk factors for endometrial cancer is crucial for prevention.Prior research suggests that pregnancy may lower endometrial cancer risk by reducing estrogen exposure.This meta-analysis aims to delve into the existing population-based longitudinal studies to evaluate the association between the time elapsed since the last birth and the risk of endometrial cancer. We searched PubMed, Cochrane Library, Embase, and Web of Science for cohort studies published up to June 21, 2024, using relevant medical subject headings (MeSH) and keywords. Statistical analyses were conducted using Stata version 14.0. A fixed-effects model was applied if P > 0.1 and I2 ≤ 50%; otherwise, a random-effects model was used to account for significant heterogeneity Publication bias was assessed using funnel plots and Egger's test. Our meta-analysis included 3 cohort studies and 5 case-control studies with a total of 3,310,734 participants, published between 1994 and 2024. The analysis revealed that time since last birth is associated with endometrial cancer risk. Specifically, a period of 0-10 years since the last birth was linked to a reduced risk of endometrial cancer (OR= 0.431; 95% CI: 0.351-0.530). A period of 10-20 years since the last birth also showed a decreased risk (OR=0.867; 95% CI:0.747-1.007), whereas more than 20 years since the last birth was associated with an increased risk (OR = 1.304; 95% CI: 1.111-1.530). Our meta-analysis indicates that a shorter time since the last birth is protective against endometrial cancer, whereas a longer interval increases risk. Further research is needed to clarify the underlying mechanisms of this association. These findings are crucial for developing new strategies for endometrial cancer prevention and treatment.